The Relationship between Self-Awareness and Results Competence of Electronic Engineering Training Participants at UPTD Payakumbuh Vocational Training Center (BLK) - Rini Rahmadani; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
in this study is the low competency results of electronic engineering training participants at the Payakumbuh Work Training Center (BLK) UPTD. self-awareness of the electronics engineering trainees. This study aims to: 1. Describe the picture of self-awareness of participants in electronics engineering training at BLK Payakumbuh, 2. Describe a picture of learning outcomes of participants in electronics engineering training at BLK Payakumbuh, 3. See the relationship between self-awareness and learning outcomes of participants in electronics engineering training at BLK Payakumbuh .This study uses a quantitative approach, with the type of correlation. The population of the study was the training participants, totaling 32 people, the sampling technique was using Simple Sampel randomly and taken 70% that is 23 people. Data collection techniques using questionnaires and data collection tools in the form of a list of statements. The data analysis technique uses Rank Order and percentage formula.The results showed that: 1) The description of the level of self-perception of the participants in the electronics engineering training course at the Payakumbuh Work Training Center (BLK) was low, 2) The description of the results was low training participants at UPTD Payakumbuh Work Training Center (BLK) was categorized as very low, 3) there is a close relationship self-awareness and learning outcomes of electronic engineering training participants at UPTD Payakumbuh Work Training Center (BLK). Hopefullyexpected in this research that the training manager be able to increase the self-awareness of the electronic engineering training participants in learning at BLK Payakumbuh.